1994
DOI: 10.1073/pnas.91.19.8925
|View full text |Cite
|
Sign up to set email alerts
|

An ethylene-responsive enhancer element is involved in the senescence-related expression of the carnation glutathione-S-transferase (GST1) gene.

Abstract: The increased production of ethylene during carnation petal senescence regulates the transcription of the GSTI gene encoding a subunit ofglutathione-S-transferase. We have investigated the molecular basis for this ethyleneresponsive transcription by examining the cis elements and trans-acting factors involved in the expression of the GSTI gene. Transient expression assays following delivery ofGSTI 5' flanking DNA fused to a P-glucuronidase reporter gene were used to functionally define sequences responsible fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
145
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(151 citation statements)
references
References 30 publications
5
145
0
1
Order By: Relevance
“…As shown in Figure 6, this region includes a near consensus TATA-box between nucleotides 194 and 200 and, notoriously, two 57-bp tandem repeated sequences (TRS1 and TRS2), sharing a 95% identity, in positions 38 to 94 (TRS1) and 95 to 151 (TRS2), respectively. A sequence motif that matches with the socalled ERE box (Itzhaki et al, 1994) was found within Figure 3. Northern analysis of TLC1.1 transcription in leaves from L. chilense plants exposed to wounding stress.…”
Section: Differential Induction Of Tlc1 Transcription By Stress-relatmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 6, this region includes a near consensus TATA-box between nucleotides 194 and 200 and, notoriously, two 57-bp tandem repeated sequences (TRS1 and TRS2), sharing a 95% identity, in positions 38 to 94 (TRS1) and 95 to 151 (TRS2), respectively. A sequence motif that matches with the socalled ERE box (Itzhaki et al, 1994) was found within Figure 3. Northern analysis of TLC1.1 transcription in leaves from L. chilense plants exposed to wounding stress.…”
Section: Differential Induction Of Tlc1 Transcription By Stress-relatmentioning
confidence: 99%
“…This 8-bp element has been previously identified as an ethylene-responsive enhancer in the tomato E4 and carnation (Dianthus caryophyllus) GST1 genes, both responsive to ethylene. Footprinting analysis has indicated that this sequence corresponds to a specific transcription factor binding site (Montgomery et al, 1993;Itzhaki et al, 1994). The participation of these putative ERE boxes in the regulation of TLC1.1 expression was demonstrated through promoter mutation analyses.…”
Section: The U3 Domain Of Tlc11 5# Ltr Includes Cis-acting Eresmentioning
confidence: 99%
“…We performed chromatin immunoprecipitation (ChIP) experiments using iE/qm plants to test this possibility. We chose three regions in the miR164A promoter containing putative EBSs (TACAT or TTCAAA) (Itzhaki et al, 1994;Konishi and Yanagisawa, 2008;Zhong et al, 2009;An et al, 2012) (Figure 6A). We found marked enrichment of EIN3 in these EBS regions, particularly the P2 site (TACAT), indicating that EIN3 binds to this region in vivo ( Figure 6B).…”
Section: Ein3 Directly Represses Mir164 Transcription In An Age-depenmentioning
confidence: 99%
“…The mechanism of ethylene-regulated genes has unraveled by molecular characterization of the promoter regions of ripening-related genes and thereby an ethylene-responsive element containing 8 bp motifs (A (A/T) TTCAAA) has been identified (Montgomery et al, 1993 andItzhaki et al, 1994). Similarly, two ethylene regulated genes, E4 and ER69 have been identified (Zegzouti et al, 1999) and these both genes are involved also in methionine cycle, encoding methionine sulphoxide reductase protein and cobalamine-independent methionine synthase respectively (Montgomery et al, 1993 andZegzouti et al, 1999).…”
Section: Ethylene Regulated Genesmentioning
confidence: 99%